Workshop on Utilizing Lemongrass (Cymbopogon citratus) for Tea and Soap for PKK Members - Widyasanti, Asri; Hafidz, Athar Zaidan; Zulkarnain, Ellysa Madina Putri; Gunawan, Fadia Hafizah; Fajri, Indra Nabil Julian; Lubis, Jessie Diorito; Fathiyah, Layyina (Journal of Community Empowerment, 2024)
The Workshop on Utilizing Lemongrass (Cymbopogon citratus) for Tea and Soap for PKK (PKK is a community organization aimed at empowering women and participating in the development of Indonesia's welfare). Members in the Pasirwangi Sub-District, Ujungberung District, Bandung City is part of the Community Service Learning (KKN) program conducted by students as a form of community service. This program aims to connect students with the local community through beneficial and practical activities, allowing them to apply the knowledge gained in college to everyday life. The activities included presentations on the making and benefits of lemongrass tea and soap, followed by demonstrations and the distribution of free lemongrass tea. The motivation from the Buruan Sae program and the habit of consuming herbal drinks made lemongrass products appealing to the community. After the workshop on lemongrass utilization, 80% of the PKK members expressed interest in making lemongrass tea or soap, based on post-test data showing their understanding of the plant's benefits. The results of this training are expected to positively impact and foster a sense of independence and creativity within the community, supporting their welfare through local products.